2022
DOI: 10.3389/fpsyg.2022.993259
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in lockdown: Understanding how music and the arts supported mental health during the COVID-19 pandemic by age group

Abstract: Recent research has indicated that many people around the world turned to artistic creative activities (ACAs) to support their mental health during COVID-19 lockdowns. However, studies have also shown that the negative psychosocial impacts of the pandemic have disproportionately affected young people, suggesting that the use of ACAs to support mental health in lockdown may have varied across age groups. This study investigated how Australians in four different age groups (18–24, 25–34, 35–54, and 55+) engaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 63 publications
(86 reference statements)
4
8
0
Order By: Relevance
“…The inclusion of music as online art engagement may have been counterproductive as it is showed as not being the most effective for people aged +65 years (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of music as online art engagement may have been counterproductive as it is showed as not being the most effective for people aged +65 years (6).…”
Section: Discussionmentioning
confidence: 99%
“…Art therapy is recognized as a valid intervention in mental health, and creativity has been incorporated into gerontology and social sciences of aging, making art practice and health in older adults the foreground of research (5). Creative activities helped to regulate emotions, in particular art and music production (6). Art participants are more likely to use the activity that they found the most helpful as a form of avoidance of negative feelings and a way to socialize with others (7).…”
Section: Introductionmentioning
confidence: 99%
“…Personal variables such as age, gender, and personality traits have been found to influence music use during the pandemic. Younger individuals (aged 18–24) were more likely to integrate music into daily life, use music for emotion regulation, respond to music in embodied ways, and use music to perform a social identity than older adults ( Chmiel et al, 2022 ). After the first COVID-19 case was confirmed in a given country, the sentiment of music accessed on Last.fm became more negative.…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, music has helped people to relax, escape, lift their mood or keep them company [47], and has functioned socially as a mode of communication that can foster a sense of belonging [48]. One study found that Australians ranked music listening as the most effective artistic creative activity for making them "feel better" during the pandemic [44], while another found that young Australians (aged 18-24) during lockdown were more likely to integrate music into daily life, use music for emotion regulation, respond to music in embodied ways and use music to perform a social identity than participants in all older age groups [49]. Another large survey of over 5000 people with representative samples from three continents found that people experiencing increased positive emotions used music for solitary emotional regulation, while those experiencing increased negative emotions used music as a proxy for social interaction [50], highlighting the widespread importance of social connection as an aspect of musical responses to the pandemic.…”
Section: Introductionmentioning
confidence: 99%